Peningkatan Daya Saing UKM Sehati Melalui Optimalisasi Penggunaan Teknologi dan Pengelolaan Manajerial - Yogi Ginanjar; Nita Hernita; Wulan Riyadi (Indonesian Community Service and Empowerment Journal (IComSE), 2021)
UKM Sehati which is used as a partner in this PKM has problems that are of special concern to find solutions. Partners do not have permanent employees who can maintain product quality, so processed products are often different from the previous taste and texture. Employees do not have extensive knowledge of recording and bookkeeping, so that the resulting financial statements are not in accordance with accounting standards. The production equipment used is still simple, both for processing aleksis (krispi catfish) and shredded catfish. The sealer machine for gluing the packaging is too small, causing the product resistance to be not optimal. The marketing that has been done has not touched the online market. The product does not yet have a halal label and nutritional value information so that the product cannot enter minimarkets and even supermarkets. Mitra's knowledge of catfish farming as a raw material has not been maximized, which causes the catfish mortality rate to reach 15%. Based on the findings regarding the problem, the priority is to find solutions to problems in improving various aspects. Among them are managerial aspects related to finance and human resources in an effort to increase community capacity. Furthermore, the technological aspects in an effort to improve product quality. Changes in marketing aspects towards digitalization and broader marketing aspects by obtaining halal labels and information on nutritional values. The specific goals and targets in this community service are to assist Sehati SMEs in improving product quality and competitiveness through the use of technology and managerial management. The method used in an effort to implement the solution above is by holding partner bookkeeping training every 2 weeks, training on the use of deep frying machines, ADR MPD 140 machines and sealer machines (so that product durability is longer and the production process is more effective and efficient), making management information system, create social media (facebook and instagram), join various e-commerce (shopee, Bukalapak, tokopedia and others), create product information website, participate in culinary exhibitions and bazaars, facilitate the inclusion of halal logos and value information nutrition in packaging, and holding training on catfish farming so that the results are maximized. The output produced is in the form of publications in the form of journals and intellectual property rights.